2023
DOI: 10.1038/s42003-023-04466-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide deposition of 6-methyladenine in human DNA reduces the viability of HEK293 cells and directly influences gene expression

Abstract: While cytosine-C5 methylation of DNA is an essential regulatory system in higher eukaryotes, the presence and relevance of 6-methyladenine (m6dA) in human cells is controversial. To study the role of m6dA in human DNA, we introduced it in human cells at a genome-wide scale at GANTC and GATC sites by expression of bacterial DNA methyltransferases and observed concomitant reductions in cell viability, in particular after global GANTC methylation. We identified several genes that are directly regulated by m6dA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In comparison, among unicellular eukaryotes, including the ciliate Tetrahymena thermophila , the green alga Chlamydomonas reinhardtii , and the early-diverging fungus Saccharomyces cerevesiae , 6mA is enriched in symmetrical ApT dinucleotides ( 57 ). Recently an experiment, using forced expression of bacterial DNA adenine-N6 MTases in human cells, demonstrated that 6mA in the context of GATC or GAnTC has a direct effect on gene expression ( 58 ).…”
mentioning
confidence: 99%
“…In comparison, among unicellular eukaryotes, including the ciliate Tetrahymena thermophila , the green alga Chlamydomonas reinhardtii , and the early-diverging fungus Saccharomyces cerevesiae , 6mA is enriched in symmetrical ApT dinucleotides ( 57 ). Recently an experiment, using forced expression of bacterial DNA adenine-N6 MTases in human cells, demonstrated that 6mA in the context of GATC or GAnTC has a direct effect on gene expression ( 58 ).…”
mentioning
confidence: 99%